Investigating risks in the delivery of water and wastewater infrastructure projects in Australia. (23rd April 2023) - Kumar, Siva; Kirytopoulos, Konstantinos
Projects related to the development of public assets usually face uncertain and changing conditions and are continuously subjected to risk and uncertainty. Wastewater and water facilities, as typical examples of public assets face such issues and the organisations involved with their delivery need to explore how to increase efficiency. This research investigates risk regarding wastewater and water projects in the Australian context. The research follows a mixed methods approach employing a literature review, focus group, anonymous questionnaire survey and investigation of specific cases. Forty-one relevant risks were identified, classified in terms of nature, lifecycle and ownership and ranked according to the Relative Importance Index. Two case studies were used for validating the findings. The results obtained expand the body of knowledge by providing knowledge regarding key risks in the area, which can be used to offer practitioners support regarding effective risk management.